1997
DOI: 10.1103/physrevb.56.3046
|View full text |Cite
|
Sign up to set email alerts
|

In situstudies of morphology, strain, and growth modes of a molecular organic thin film

Abstract: We use grazing incidence x-ray scattering to study the molecular structure and morphology of thin ͑Ͻ70 ML͒ crystalline films of 3,4,9,10-perylenetetracarboxylic dianhydride ͑PTCDA͒ on Au͑111͒ surfaces as a function of film thickness, substrate temperature, and growth rate. Although the first two PTCDA monolayers grow in a layer-by-layer fashion, the film evolution beyond the second monolayer depends strongly upon the growth conditions resulting in low-temperature ͓i.e., nonequilibrium ͑NEQ͔͒ and high-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
128
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 26 publications
15
128
3
Order By: Relevance
“…Compared to the PL obtained from single PTCDA crystals, 21,22 the PTCDA film shows a very similar PL structure; however, the whole emission is shifted to lower energies by approximately 20 meV. A possible explanation for this redshift might be different strain within the film 40 and in the single crystals. Furthermore, the PTCDA film reveals a more pronounced highenergy band at 1.95 eV compared to the PTCDA crystals.…”
Section: Resultsmentioning
confidence: 91%
“…Compared to the PL obtained from single PTCDA crystals, 21,22 the PTCDA film shows a very similar PL structure; however, the whole emission is shifted to lower energies by approximately 20 meV. A possible explanation for this redshift might be different strain within the film 40 and in the single crystals. Furthermore, the PTCDA film reveals a more pronounced highenergy band at 1.95 eV compared to the PTCDA crystals.…”
Section: Resultsmentioning
confidence: 91%
“…For the Au(111) surface, it has been found that the molecule does not form monolayers commensurate with the substrate but rather exhibits a point-on-line growth on the (22 × √ 3) reconstructed surface [27]- [30]. Inclusion of these effects in the present calculations is hampered by the excessive computational effort arising from the required huge supercells.…”
Section: System Specificationsmentioning
confidence: 97%
“…[12][13][14] With respect to its chemical structure, DIP is a relatively simple, planar hydrocarbon without heteroatoms. In contrast to the intensely studied perylene derivative [15][16][17][18][19][20] 3,4,9,10-perylene tetracarboxylic dianhydrid (PTCDA, C 32 H 8 O 6 ) with its four keto groups, the DIP-substrate interaction is not complicated by polar side groups, and the influence of intermolecular interactions is expected to be smaller than for PTCDA. 21 Here, we present a systematic study with high-precision experimental data and state-of-the-art calculations of DIP adsorbed on Cu(111), Ag(111), and Au(111).…”
Section: Introductionmentioning
confidence: 93%